The truth about the World : (McGraw Hill, 2011)
This collection of essays addresses some of the most important issues in philosophy, involving God, the mind, freedom, knowledge, and ethics. It can accompany James Rachels and Stuart Rachels’ introductory text, Problems from Philosophy, or it can stand alone with great effectiveness. The Truth about the World and Problems from Philosophy were James Rachels’ last contributions to philosophy, and each book has been revised by his son, Stuart. In these two books, James Rachels found a culminating expression for his love of philosophy.